2001
DOI: 10.1097/00007632-200107010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Facet Joint Denervation in the Treatment of Low Back Pain

Abstract: Although radiofrequency facet joint denervation may provide some short-term improvement in functional disability among patients with chronic low back pain, the efficacy of this treatment has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
267
0
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(279 citation statements)
references
References 36 publications
3
267
0
9
Order By: Relevance
“…One study investigated 70 patients (36 neurotomy, 34 placebo lesion) who had had a successful intraarticular diagnostic block ("significant pain reduction for 24 hours") with lidocaine/Triamcinolone (Leclaire et al 2001). Minor (p=0.05) positive and short-term (4 weeks) improvements were observed for disability (Roland and Morris scale), but there was no effect on pain (VAS) and Oswestry scale.…”
Section: Effectiveness Of Radiofrequency Facet-denervation Versus Shamentioning
confidence: 99%
See 1 more Smart Citation
“…One study investigated 70 patients (36 neurotomy, 34 placebo lesion) who had had a successful intraarticular diagnostic block ("significant pain reduction for 24 hours") with lidocaine/Triamcinolone (Leclaire et al 2001). Minor (p=0.05) positive and short-term (4 weeks) improvements were observed for disability (Roland and Morris scale), but there was no effect on pain (VAS) and Oswestry scale.…”
Section: Effectiveness Of Radiofrequency Facet-denervation Versus Shamentioning
confidence: 99%
“…This was not done in one of the trials included in formulating these guidelines (Leclaire et al 2001).…”
Section: Commentsmentioning
confidence: 99%
“…On the one hand, Leclaire et al reported that the procedure is effective in terms of pain improvement only in the short term (4 weeks after the procedure) and the improvement failed to last even beyond 12 weeks [8]. Other studies supported these data, including one recently published in the Lancet [1,6,8]. On the other hand, other authors showed long-term improvement in pain even for years after the procedure [4,17,19,22].…”
Section: Introductionmentioning
confidence: 97%
“…The principle is production of heat in order to damage some or all nerve fibers in the target nervous structure (in the case of "conventional" RF) or application of an electromagnetic field to the nervous structure (in the case of pulsed RF), with the ultimate aim of blocking transmission of pain stimuli from peripheral receptors to the central pain structures. In recent years, some publications have reported contradictory results following RF treatment of back pain [1,4,6,8,17,19,22]. On the one hand, Leclaire et al reported that the procedure is effective in terms of pain improvement only in the short term (4 weeks after the procedure) and the improvement failed to last even beyond 12 weeks [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation